Effect of various binding agent and tableting technique on physical properties of stevia effervescent tablets - Dr. Mimi Sakinah, Abdul Munaim; Farahazwani Izazi, Mohamad; Yi Ling, Goh; Syasya Amyra, Suhana; Nur, Athirah (2021)
An effervescent tablet based on stevia was formulated. Stevia has a low-calorie sweetener with antioxidant and antidiabetic properties. Three methods to prepare the stevia effervescent tablet, which are direct compression method, wet granulation method and dry granulation method.The effervescent tablet includes stevia, acidifying agent, alkalizing agent, and binding agent.